Relationship between Neck Circumferences with Cardiovascular Risk Factors - N Bizheh (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Cardiovascular diseases that are the most common causes of mortality worldwide can be recognized and prevented through measurement of some anthropometric indices. Relationship of many anthropometric indices with cardiovascular diseases risk factors has been well documented. The aim of this study was to introduce a novel anthropometric index that can be used more easily and accurately. METHODS: This cross sectional study was performed on 179 healthy and inactive men and women selected from individuals referring to cardiovascular department of Imam Reza hospital of Mashhad for normal heart checkup under supervision of a cardiovascular surgeon. Their anthropometric indices (neck circumference, waist circumference, weight, body mass index, waist to hip ratio) and atherosclerosis risk factors (lipids and glucose) was determined. Then the relationship between anthropometric indices and atherosclerosis risk factors was determined.FINDINGS: Results showed positive and significant correlation between neck circumference with TC/HDL, TG, TG/HDL and VLDL, waist circumference with glucose, TG and VLDL, body mass index with TC/HDL and TG/HDL and waist to hip ratio with glucose (p<0.05). In men neck circumference with LDL, VLDL, TG, TC/HDL, TC and TG/HDL and waist circumference with LDL, LDL/HDL, TC, TC/HDL, TG, TG/HDL and VLDL had positive and significant correlation and waist to hip ratio had negative and significant correlation with HDL (p<0.05).CONCLUSION: According to the results of this study, neck and waist circumference had more precision in predicting of atherosclerosis risk than other indices, thus we can use these indices especially neck circumference that is simpler for determination of atherosclerosis risk in middle aged women and men.